Tax confiscation and Ecclesiastical exemption of the IBI (Real Estate Tax) - Verdoy, SJ, Alfredo (Razón y fe, 2018)
The IBI (Real Estate Tax), which is administered by the local government, has become another weapon to most of the Spanish public opinion. In this editorial we offer, from the point of view of Public Finances, the Spanish law practice and tradition, the political life and the Church’s welfare obligations and transparency, a reconstruction of the polemic, a polemic which is clearly political and economic, as well as possible solutions.